(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
Ancient greek tragedy notoriously provided director Luchino Visconti and his screenwriters with invaluable inspiration while they were writing Sandra. Working on unpublished documents and collating six different versions of the screenplay, this essay aims to establish when and in which ways the three versions of the Atridis’s myth by Aeschylus, Sophocles and Euripides exactly influenced Visconti’s project and how they contributed to its basic ambiguity. At the same time, it shows the relevance of others suggestions of the antiquity, and in particular that of Etruscans inspired by Gabriele D’Annunzio’s novel Forse che sì forse che no.